Integration of Aswaja Values for Intolerance Prevention in Madrasah Ibtidaiyah: A Study of Curriculum and Teachers' Pedagogical Practices - Abdul Karim; Moh. Dasuki; Zainal Abidin; Muhammad Kashif Majeed (Bidayatuna, 2026)
The phenomenon of intolerance and hate speech in Madrasah Ibtidaiyah (Islamic elementary schools) is precipitated by a deficiency in understanding of diversity, an exclusionary environment, and the deleterious influence of social media. The present study aims to analyze the integration of religious moderation values into the Aswaja (Ahlussunnah wal Jama'ah) curriculum, teachers' strategies for instilling moderation, and the impact on developing students' inclusive and reflective attitudes. A qualitative approach, employing a case study design, was utilized in this study. The data were collected through observation and interviews, analyzed using the Miles-Huberman-Saldana model, and validated through triangulation and member checks. The findings reveal that: The Aswaja curriculum has been found to comprehensively integrate the principles of tawassuth (moderation), tasamuh (tolerance), i'tidal (balance), and ukhuwah (brotherhood) into its content, objectives, and learning practices with the aim of preventing intolerance. Teachers' strategies for instilling moderation are implemented through curricular activities, such as discussions of Aswaja values, social reflection, and real-life connections. Co-curricular activities include reflective videos, simulations, and case studies. Extracurricular activities, such as joint ceremonies and IPPNu activities, round out the implementation of this strategy. The findings of this study demonstrate that Aswaja learning fosters social inclusiveness, reduces negative behaviors, develops reflective-empathic attitudes, and internalizes moderation values in students' daily lives. The study's findings indicate that the Aswaja curriculum plays a pivotal role in fostering intolerance prevention by integrating moderation values, multidimensional strategies, and the cultivation of inclusive attitudes. The efficacy of this curriculum is contingent upon the pedagogical competence of the teachers, the effectiveness of role modeling, and the implementation of reflective approaches. The present study makes a significant contribution to the field of social constructivism and transformative learning theories by offering an integrative model of curricular, co-curricular, and extracurricular learning. This model is designed to instill religious moderation, tolerance, and inclusive attitudes.